THE PRACTICE OF HIBAH AS A SUBSTITUTE HEIR AMONG THE JAVANESE FAMILY - Sukiati Sukiati (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2018)
Abstract: This paper is an attempt to discuss the tradition of bequest or hibah as an inheritance, in which the wealth is distributed before the parents passed away among Javanese Family in Selesai Langkat. Data collection used qualitative method and phenomenology approach. Data analysis used descriptive analysis. The data from the field was collected, processed, reduced and then concluded. It is concluded that there are three patterns of giving hibah: the first, the treasure is granted entirely to the heirs before the heirs passed away. The surviving heir is usually set aside for living expenses and needs. The heir is usually living with the youngest child called, the ‘ragil.’ When he dies, the child who tookcare will inherit the wealth. Second, inheritance is distributed after the heir dies. Third, families who are prosperous in terms of economics usually give grants to all children in the form of fields and houses.Abstrak: Praktik Hibah sebagai Ahli Waris Pengganti di Kalangan Masyarakat Jawa. Tulisan ini bertujuan mendiskusikan tradisi memberikan hibah sebagai harta warisan, di mana pewaris sendiri belum meninggal dunia, di kalangan Masyarakat Jawa Selesai Langkat. Data dikumpulkan dengan menggunakan metode kualitatif dengan pendekatan fenomenologi. Data dianalisis secara deskriptif. Data dari lapangan dikumpulkan, diolah, direduksi dan ditarik kesimpulan. Tulisan ini menyimpulkan terdapat tiga pola pemberian hibah sebagai pengganti harta warisan. Pertama, harta dihibahkan seluruhnya kepada ahli waris sebelum pewaris meninggal dunia. Bagian pewaris yang masih hidup biasanya disisihkan untuk biaya hidup dan kebutuhannya. Pewaris biasanya tinggal bersama anak ragil (bungsu). Bila ia meninggal dunia, maka anak yang merawatnya inilah yang mewarisi bagiannya. Kedua, harta warisan dibagikan setelah pewaris meninggal dunia. Ketiga, keluarga yang cukup sejahtera dari segi ekonomi biasanya memberi hibah kepada semua anaknya berupa ladang dan rumah.Keywords: Islamic jurisprudence, hibah, substitute heirs, inheritance, Java family